Physiological and tactical on-court demands of water polo - Botonis, G. P.; Toubekis, G. A.; Platanou, I. T. (The Journal of Strength and Conditioning Research, 2019)
The purpose of the present review is to provide a quantification of the specific game's activities performed by elite water polo players and a comprehensive overview of the physiological requirements reflecting physical and tactical on-court demands in water polo. Game analysis demonstrates that various swimming movements occur throughout a match play, although approximately 50% of these are recorded in horizontal body position. The various offensive and defensive tactical actions transiently modify the playing intensity, which overall corresponds to the players' lactate threshold. Even play corresponds to 60% of total game actions, whereas the respective percentage of power-play and counterattacks may exceed 30%. The ability to perform high-intensity activities with short recovery periods is critical for water polo players. Elite water polo players present a high level of aerobic power and endurance as indicated by their maximal oxygen uptake and speed at the lactate threshold. Depending on the positional roles, outfield players are characterized as centers or peripherals. The overall physiological load seems to be similar between players at various positions, despite that centers execute more dynamic body contacts, whereas peripherals more swimming bouts. Despite limitations concerning the experimental setting, the current findings indicate that the incidence of fatigue deteriorates playing intensity and performance. Nonetheless, data from the reviewed studies should be cautiously interpreted because in some of the studies, players' substitutions were not allowed. A high conditioning level is essential for water polo, as it is associated with superior technical and tactical efficacy and lower decline of physical or technical performance within the game.